Customização do afastador de Langenbeck reverso utilizando tecnologia 3D e avaliação da sua aplicação em cirurgias ortognáticas com osteotomia sagital do ramo mandibular - Uchôa, Caio Pimenteira (2023)
Orthognathic surgeries are usually indicated for the treatment of dentofacial deformities and aim to adapt occlusal conditions and improve the patient's facial harmony. The Sagittal Osteotomy of the Mandibular Branch (OSRM), due to its versatility and wide application, has been receiving modifications and evolution over the years, in the same way it is necessary to develop new surgical instruments that will satisfactorily meet these new techniques, causing less trauma to surgical tissues and which can, in this way, provide greater comfort, speed and ease in carrying out the surgical procedure. Therefore, in the present study, the customization of a pre-existing device was proposed to perform sagittal osteotomy of the mandibular ramus and its evaluation during surgery. Develop and evaluate the use and changes made to the instrument during sagittal osteotomy of the mandibular ramus in orthognathic surgery and evaluate the quality and level of patient satisfaction in the postoperative period. A qualitative and experimental analytical study was carried out, in which reinterpretations of the design of the conventional reverse Langenback retractor used in orthognathic surgeries were developed, using the Autodesk Inventor Processional® software version 2021 and through additive manufacturing, printed test prototypes, after approval of the modifications based on the limitations existing in the traditional instruments used, the new retractor was made of stainless steel. Through surgeries and questionnaires applied to Oral and Maxillofacial Surgeons and orthognathic patients at the Dom Luiz Gonzaga Fernandes Emergency and Trauma Hospital located in the City of Campina Grande – PB, modifications to the device itself and post-operative quality were evaluated and the data were treated statistically by the SPSS version 23.0 program. The results showed, in the operators' view, that for 100% the customization of the retractor facilitated the use of drills and saws during OSRM and for 71.4% the appropriate maintenance of protection for noble structures and adjacent soft tissue, however for the surgeon with a greater number of surgeries per year, the modifications carried out did not generate less separation of soft tissues, revealing a statistically significant analysis (p=0.02). In patient evaluations, an excellent level of post-operative satisfaction was noted. Furthermore, during the procedure there were no complications or accidents directly related to the use of the retractor. The proposed modified instrumentation proved to be effective for clinical-surgical purposes, considering the existing space limitation and the better access in the region provided by the instrumentation used in the study.